Optimal design of magneto-rheological damper comparing different configurations by finite element analysis - Ferdaus, Mohammad Meftahul; Rashid, Muhammad Mahbubur; Hassan, Muhammad Hasibul; Rahman, Mohammed Ataur (Springer, 2014)
Magnetorheological (MR) damper is one of the most advanced applications of semi active damper in controlling vibration. Due to its continuous controllability in both on and off state its practice is increasing day by day in the vehicle suspension system. MR damper’s damping force can be controlled by changing the viscosity of its internal magnetorheological fluids (MRF). But still there are some problems with this damper such as MR fluid’s sedimentation, optimal design configuration considering all components of the damper. In this paper both 2-D Axisymmetric and 3-D model of MR Damper is built and finite element analysis is done for design optimization. Different configurations of MR damper piston, MR fluid gap, air gap and Dampers housing are simulated for comparing the Dampers performance variation. From the analytical results it is observed that among different configurations single coil MR damper with linear plastic air gap, top and bottom chamfered piston end and medium MR fluid gap shows better performance than other configurations by maintaining the same input current and piston velocity. Further an experimental analysis is performed by using RD-8041-1 MR Damper. These results are compared with the optimized MR Damper’s simulation results, which are clearly validating the simulated results.